Pentingnya Pendidikan Kewarganegaraan dalam Memberikan Pemahaman Tentang Budaya Demokrasi dan Toleransi - Munandar, Agus; Wibisono, Eko; Fiqri, Ahmad; Japar, M; Kardiman, Yuyus (Universitas Syiah Kuala, 2025)
Civics education plays a strategic role in fostering an understanding of democratic culture and the values of tolerance. Civics education plays a crucial role in shaping a young generation that is politically intelligent, responsible, and active in building a healthier democracy. Civics education not only teaches democratic theories but also provides students with opportunities to participate directly in various social and political activities, which can enrich their understanding of democratic processes and citizenship. Civics education is a crucial tool for building an inclusive democratic society. By increasing social and political participation and strengthening trust in public institutions, civics education can foster the values of tolerance and diversity that are so desperately needed in an increasingly complex society. Civics education, which not only teaches political knowledge but also provides direct experience in social and political participation, plays a crucial role in fostering a culture of democracy and tolerance among the younger generation.